Nonfatal childhood injuries and their association with socioeconomic and gender structures: an ecological study of 14 Swedish municipalities (2000–2005) (Italian Journal of Public Health, 2011)
Background: Injuries are the major cause of death and disability in European children. This study exploredsocioeconomic and gender structures in association with nonfatal childhood injury rates by sex and agegroups in Sweden.Methods: Six indicators of socioeconomic structure and three indicators of gender structure were combinedusing principal component analysis. Sex- and age-specific mean annual injury rates of fourteen Swedishmunicipalities were estimated (2000–2005). The associations were analysed with Pearson’s correlationcoefficients.Results: Narrow gender ratio in unskilled occupations and in politics was positively associated with injuriesin girls 6–17 years (r ≥ 0.7) and with fractures in boys 6–12 years of age (r = 0.5). Wider income distributionwas negatively associated (r ≥ -0.4) with boys’ injuries and positively associated with fractures in girls 13–17years (r = 0.5). Relative wealth and male manager dominance was negatively associated with injuries inchildren 0–5 years (r = -0.4). Relative poverty was not associated with nonfatal childhood injuries.Conclusions: The strength of the associations between socioeconomic and gender structures and nonfatalchildhood injury rates varied by sex, age group and type of injury. Childhood injury preventive interventionsshould consider the local gender structure, area-level wealth and area-level income distribution, and notonly area-level poverty.
Keywords: children; injuries; socioeconomic structure; gender structure; ecological study